Heat and mass transfer analysis for MHD bioconvection peristaltic motion of Powell-Eyring nanofluid with variable thermal characteristics - Iqbal, J.; Abbasi, F.M.; Alkinidri, M.; Alahmadi, H. (Case studies in thermal engineering, 2023)
Present study describes the influences of mass and heat transfer on Magnetohydrodynamics (MHD) bioconvective peristaltic transport of Powell-Eyring nanofluid through a curved channel with radius dependent magnetic field. Modified Darcy's law, Ohmic heating, motile gyrotactic microorganisms, thermal radiation, variable properties, Brownian and thermophoresis motion are also considered. Furthermore, velocity and thermal slip conditions were employed in the analysis. The phenomenon of motile microorganisms enhances the stability of nanoparticles as well as improves heat transfer. The microorganism concept is accepted only for the stabilization of suspended nanomaterials due to bioconvection, which is facilitated by combined impacts of a magnetic field and buoyancy forces. Modified Darcy's law is used to model flow through a porous space. Governing equations for the proposed model are simplified by using lubricant approximations. NDSolve (built-in command in Mathematica) is used to obtain the numerical solutions for axial velocity, concentration profile, density of motile microorganism distribution, magnitude of temperature, analysis of heat and mass transfer. Obtained results are presented graphically for different values of flow quantities of interest. The results report that increasing the radiation and variable viscosity parameters diminishes the nanofluid temperature. It is observed that heat transfer rates are enhanced by improving heat source/sink and Powell-Eyring fluid parameters. Outcomes reveal that a growth in curvature and Hartman number reduce the axial velocity of nanofluid. Moreover, concentration distribution improves for larger values of the Brownian motion coefficient. The density of motile microorganisms drops by increasing bioconvection Peclet number. Mass transfer rates slightly improves when Hartman number is increased. In addition, results for the planner channel can be attained for the larger values of curvature parameter. •Heat and mass transfer analysis for bioconvective peristaltic transport of non-Newtonian nanofluid through a curved conduit is carried out in this study.•Magnetohydrodynamic study for the case of radius dependent magnetic field is incorporated.•Modified Darcy's law, Ohmic heating, motile gyrotactic microorganisms, thermal radiation, variable properties, Brownian and thermophoresis motion are accounted.•The phenomenon of motile microorganisms enhances the stability of nanoparticles as well as improves heat transfer.•Results report that increasing the radiation and variable viscosity parameters diminishes the nanofluid temperature.